A description of two outbreaks of capripoxvirus disease in Mongolia - Beard, P.M. (Elsevier Scientific Pub. Co, 2010)
Mongolia had no reported cases of capripoxvirus disease from 1977 until an outbreak of sheeppox in 2006–2007 and then goatpox in 2008. The two outbreaks occurred in geographically distant areas of Mongolia and, most strikingly, were highly species-specific. The 2006–2007 sheeppox outbreak affected no goats and the 2008 goatpox outbreak affected no sheep despite communal herding. The diseases were diagnosed using the polymerase chain reaction and virus neutralisation test. The P32 gene of the Mongolian sheeppox and goatpox viruses from the recent outbreaks were sequenced and compared with an archived 1967 strain of Goatpox virus from Mongolia. The P32 gene of the 2006–2007 Mongolian Sheeppox virus strain was identical to previously published sheeppox strains. The P32 gene of the 2008 Mongolian Goatpox virus strain was identical to the gene from virus isolated from recent goatpox outbreaks in China and Vietnam. The archived Mongolian Goatpox virus strain was unique.